ANALISIS KONSUMSI PANGAN DAN STATUS GIZI DENGAN TINGKAT KELELAHAN PADA ANGGOTA UNIT KEGIATAN MAHASISWA JUJITSU DOJO UNESA - Setyoko, Gigih (Jurnal Kesehatan Olahraga, 2019)
Jujitsu is one of the sport of martial arts that require high energy in practice. This martial sport is one of the sports that are anaerobic. Institute of Jujitsu Dojo Unesa is one of UKM of martial arts-hosted State University of Surabaya. The majority of the members of the UKM Jujitsu Dojo Unesa which follow the exercises are students who come from outside the city. So it's likely the food consumption less meet nutritional needs. Based on the foregoing, the researchers conducted a study entitled analysis of food consumption and nutritional status to the level of fatigue on the members of student activity units Jujitsu Dojo Unesa. This research is a descriptive quantitative research using this type of approach of cross sectional. The samples on this research as many as 18 people. Research results known to the average food consumption Jujitsan Dojo Unesa 77,78% average (the deficit), nutritional status of 77,78% (normal), and the level of fatigue 55,56% (much less) with the results of the test data showed normality Gaussian i.e. the results are significant at 0,154. The correlation test showed that there is a significant relationship between food consumption, nutrient status, and level of fatigue. Where the level of nutritional status has a negative correlation value on food consumption and physical activity, while food consumption has a positive correlation value on physical activity and level of fatigue. Conclusions in this study i.e., there is a significant relationship between food consumption, nutrient status, and level of fatigue. Keywords:Nutritional Status, Food Consumption, Levels of Fatigue, Jujitsan